Inclusive public participation in health: Policy, practice and theoretical contributions to promote the involvement of marginalised groups in healthcare - de Freitas, C (2015)
Migrants and ethnic minorities are under-represented in spaces created to give citizens voice in healthcare governance. Excluding minority groups from the health participatory sphere may weaken the transformative potential of public participation, (re)producing health inequities. Yet few studies have focused on what enables involvement of marginalised groups in participatory spaces. This paper addresses this issue, using the Participation Chain Model (PCM) as a conceptual framework, and drawing on a case study of user participation in a Dutch mental health advocacy project involving Cape Verdean migrants. Data collection entailed observation, documentary evidence and interviews with Cape Verdeans affected by psychosocial problems (n = 20) and institutional stakeholders (n = 30). We offer practice, policy and theoretical contributions. Practically, we highlight the importance of a proactive approach providing minorities and other marginalised groups with opportunities and incentives that attract, retain and enable them to build and release capacity through involvement. In policy terms, we suggest that both health authorities and civil society organisations have a role in creating 'hybrid' spaces that promote the substantive inclusion of marginalised groups in healthcare decision-making. Theoretically, we highlight shortcomings of PCM and its conceptualisation of users' resources, suggesting adaptations to improve its conceptual and practical utility.